Multicultural Interpretation and Hermeneutics of Islamic Education Philosophy: Frithjof Schuon's Perennialism Perspective in Urban Society - Muhammad Abdul Anam; Hamdanah Hamdanah; Mazrur Mazrur (Jayapangus Press, 2026)
Urban communities face complex challenges in Islamic education due to cultural diversity and tendencies toward religious formalism. As a multi-ethnic city, Palangka Raya requires an inclusive and spiritually meaningful approach to Islamic education. This article analyses the role of multicultural interpretation and philosophical hermeneutics in urban Islamic education through the perspective of Frithjof Schuon's perennialism. This study uses a qualitative approach based on literature studies contextualized with the social reality of Palangka Raya and supported by limited interviews with educators and Islamic education figures. The analysis was conducted interpretively through philosophical synthesis. The results of the study show that multicultural interpretation functions as an inclusive ethical framework, philosophical hermeneutics encourages dialogical and contextual understanding, while Schuon's perennialism becomes a metaphysical foundation that integrates the exoteric and esoteric dimensions. The novelty of this research lies in the formulation of an integrative epistemological framework for the development of Islamic education in urban communities.